Poly(m-phenylene isophthalamide)-graphene oxide composite separators: A pathway to safer and high-performance lithium-ion batteries - Haneum Kim; Eunseo Jeon; Yangyul Ju; Jinyoung Chun; Doojin Lee (Polymer Testing)
Safety concerns remain a major challenge for lithium-ion batteries (LIBs), particularly due to the poor thermal stability and flame retardancy of commercial polyolefin separators. To address these issues, we propose a separator modification technique using a composite of poly(m-phenylene isophthalamide) (PMIA) and graphene oxide (GO) to enhance thermal stability, flame retardancy, and electrolyte wettability. The PMIA-GO coating leverages the excellent heat resistance of PMIA and strong hydrogen bonding between PMIA and GO to improve thermomechanical strength and structural integrity at high temperatures. The microporous structure acts as an electrolyte reservoir, while oxygen-functional groups increase wettability, enhancing ionic transport and electrochemical performance. LIBs assembled with PMIA-GO nanocomposite separators exhibit superior ionic conductivity, cycling stability, and capacity retention, as well as durable thermomechanical properties, outperforming conventional PE separators.